Redefining Motherhood: How Formerly Incarcerated Black Mothers Frame Mothering Choices. (October 2022) - Banks, Erica
Black mothers have never fit the hegemonic white standard of motherhood. The bad mother narrative has been superimposed on Black women through controlling images. Through in-depth interviews with formerly incarcerated Black mothers, I demonstrate how formerly incarcerated Black women invert controlling images through how they frame their mothering choices. Their reframing of their mothering choices reveals that formerly incarcerated Black mothers have mothering practices that entail good mothering and goes beyond the white imaginary. These mothering practices reveal a redefinition of motherhood that provides greater understanding of how formerly incarcerated Black mothers understand and make sense of their mothering choices.